Massive Mimo Technology And Heterogenous Network: Promising Proposals for High Data Rate Wireless Communications - Duong , Hiển Thuận (Journal of Technical Education Science, 2018)
Wireless communication is one of the most popular technologies in recent years and the demand for high data rate transmission is growing, and it is expected that in 2020 the download speed of the 5G network is 10Gbps. Massive MIMO has been identified as a key technology to handle orders of more data traffic (increasing spectral efficiency) by the number of antennas used. Heterogeneous networks (HetNETs) or dense networks are considered candidates for increased energy efficiency depending on the density of the stations. In which, the small cell architecture and soft cell approach are concerned much by a lot of researchers due to their significantly improving the uplink capacity. In this paper, we evaluate the advantages of these two proposals and combine them together through the optimization tool Matlab CVX.